REFLEXÕES SOBRE A JUVENTUDE FRENTE A PRECARIZAÇÃO DA EDUCAÇÃO E DO TRABALHO (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
Characterized by many changes, the scenario of economic crisis in Brazil has mainly affected young people. With worsening poverty rates, dropping out of school and precarious work, young people have been suffering from high levels of unemployment and an education that has an exclusionary profile. Given this, the objective of the present article is to broaden the view about this complex reality that presents numerous recessions placed on young people that directly interfere with their future and their perception. Assuring a reflection analytical that seeks proposals for the emancipation of young people, considering this to be a historical duty of the State, family and society, the construction of the text, based on exploratory bibliographic research, highlights indispensable factors for overcoming poverty, but which, with The neoliberal perspective adopted by the state is in the background. It is possible to understand that dilemmas inherent in this moment, such as going to work and / or studying, entering a college, living with parents or leaving home, are in fact decisions conditioned by the complex capitalist system that does not have equal opportunities for everyone and thus maintains the same conditions. unequal social relations that circulate, even today.